DEMOGRAPHIC AND BEHAVIORAL PROFILING OF E-WALLET USERS: A COMPARATIVE ANALYSIS OF E-WALLET PLATFORMS - Shao Wei Koh; Adriana Shamsudin; Thanasilan Ong; Alea Nurhazli; Farhanah Muhamad; Yusma Fariza Yasin (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The revolution of the internet has given rise to the development of electronic wallets (E-Wallets). This digital version of the physical wallet has gained popularity due to its convenience, security, and ease of use. The Malaysian government has launched many campaigns and initiatives to support the transformation of traditional payment methods to cashless payment methods resulting in competitive markets within the total 42 E-wallet providers. In this study, we identify and contrast the specific demographic and behavioral profiles of users across different popular e-wallet platforms. This study was carried out quantitatively by analyzing the Google form survey data obtained from 180 Malaysian respondents based on different platforms. The analysis shows that overall Touch N Go has recorded the highest usage among the users at 51.11% followed by MAE and other platforms at 28.33% and 20.56% respectively. This result is consistent with the demography on gender, location, employment, income, and education level except in demography on age, rating of e-wallet usage purpose, and perception of the e-wallet. Our finding also addressed that a sample size of 180 respondents was not sufficient to fully represent the entire population of Malaysia. Therefore, the adoption of a stratified sampling method consisting of all states within Malaysia is more appropriate.